The Variants of the MGSS Methods for Complex Symmetric Linear System of Equations (Communications in Mathematical Research, 2025)
Recently, inspired by a modified generalized shift-splitting iterationmethod for complex symmetric linear systems, we propose two variants of themodified generalized shift-splitting iteration (MGSS) methods for solving complex symmetric linear systems. One is a parameterized MGSS iteration methodand the other is a modified parameterized MGSS iteration method. We provethat the proposed methods are convergent under appropriate constraints onthe parameters. In addition, we also give the eigenvalue distributions of different preconditioned matrices to verify the effectiveness of the preconditionersproposed in this paper.
Keywords: Complex symmetric linear system; variants of MGSS method; convergence analysis.